An NMR Study of the Bortezomib Degradation under Clinical Use Conditions. (14th April 2009) - Bolognese, Adele; Esposito, Anna; Manfra, Michele; Catalano, Lucio; Petruzziello, Fara; Martorelli, Maria Carmen; Pagliuca, Raffaella; Mazzarelli, Vittoria; Ottiero, Maria; Scalfaro, Melania; Rotoli, Bruno
Abstract : The (R)-3-methyl-1-((S)-3-phenyl-2-(pyrazine-2-carboxamido)propanamido)butyl-boronic acid, bortezomib (BTZ ), which binds the 20S proteasome subunit and causes a large inhibition of its activity, is a peptidomimetic boronic drug mainly used for the treatment of multiple myeloma. CommercialBTZ, stabilized as mannitol derivative, has been investigated under the common conditions of the clinical use because it is suspected to be easily degradable in the region of its boronic moiety. CommercialBTZ samples, reconstituted according to the reported commercial instructions and stored at4 ∘ C, were analyzed by high-field nuclear magnetic resonance spectroscopy in comparison with identical samples bubbled with air and argon, respectively. All the samples remained unchanged for a week. After a month, the air filled samples showed the presence of two main degradation products (6% of starting material), the N-(1-(1-hydroxy-3-methylbutylamino)-1-oxo-3-phenylpropan-2-yl) pyrazine-2-carboxamide (BTZ1 ; 5%, determined from NMR integration) and the (S)-N-(1-(3-methylbutanamido)-1-oxo-3-phenylpropan-2-yl)pyrazine-2-carboxamide (BTZ2 ; 1%, determined from NMR integration), identified on the basis of their chemical and spectroscopic properties. TheBTZ1 andBTZ2 finding suggests that, under the common condition of use and at4 ∘ C, commercial BTZ-mannitol is stable for a week, and that, in time, it undergoes slow oxidative deboronation which partially inactivates the product. Low temperature and scarce contact with air decrease the degradation process.